Désinstitutionnalisation : son impact sur l’efficacité et l’efficience: Deinstitutuinalization: its impact on the efficacity and the efficiency - Roy, Sarto; Cloutier, Renaud (Revue francophone de la déficience intellectuelle, 1994)
Le présent article décrit, à l’aide des 26 indicateurs proposés par un groupe de travail sur l’évaluation de programmes de la Fédération Québécoise des centres de réadaptation pour les personnes présentant une déficience intellectuelle (FQCRPDI), l’impact du mouvement de désinstitutionnalisation sur l’efficience et l’efficacité organisationnelle d’un centre de réadaptation québécois. Les constats confirment les changements profonds dans les pratiques administratives et cliniques de ce centre et la capacité des indicateurs à rendre compte des changements organisationnels. Abstract This study presents the effects of deinstitutionalization upon twenty-six indicators of performance. Those indicators were developped by an expert group working in different rehabilitation centers for persons Iiving with mental handicaps in the province of Quebec in Canada. Most of those indicators moved in a more efficient way and indicated a major changing in administration and clinical practices of the rehabilitation center under study after deinstitutionalization. Those indicators seem clearly indicated and resumed the situation about organisationnaI changing before and after deinstitutionalization.